“Let the Reader Understand”: Ancient Pedagogy and the Social Setting of Mark - Hubbard, Jeffrey M. (Novum Testamentum, 2023)
Mark’s only direct reference to the reader of his Gospel (Mark 13:14) has long fascinated interpreters. But what kind of reading event is presumed in this authorial aside? This essay compares Mark 13:14 to similar interpretive asides from the commentarial traditions of ancient schools. Through analysis of relevant material from Epictetus, the author of this essay demonstrates that a reader’s comprehension of authoritative texts was a primary objective of ancient education. He further shows that the practice of drawing a reader’s attention to particular interpretive conundrums is well evidenced in ancient commentaries like Origen’s Commentary on Matthew and the commentaries of Philo. The author argues that this evidence from pedagogical reading events can fruitfully illuminate Mark 13:14, and can help us to theorize better about the social setting of Mark’s Gospel.